Pendampingan Pemanfaatan Ampas Tahu Menjadi Produk Pangan Bernilai Ekonomi Tinggi Bagi Masyarakat Pengusaha Tahu di Gerisak Mataram - Muti'ah Muti'ah; Jeckson Siahaan; Eka Junaidi; Sukib Sukib (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2022)
A social works as accompanion to use solid tofu’s waste to be a high economic value food products for enterpreuners society of tofu in Gerisak, Mataram has already conducted recently. The society who were involved in this activities are house wife who are gathered in a group of tofu home industry enterpreunership as a number of 12 - 15 members. Activities were already done as follows: production of tofu crepes, lecturing, and discussion. The results of these activities are: (1) succed to do lecturing of the way to produce crepes from solid tofu’s waste base. This is showed by the results of lecturing such as interesting and motivation of members society. (2) succed to produce tofu’s crepes from solid tofu!s waste base through some steps such as preparation of materials, mixing, boiling, ctting, and drying. From the result of evaluation is known that to improve the taste it is needed adding of a small amount of onion. (3) succed to conduct discussion; this is showed by the results of discussion such as increasing of motivation to produce tofu’s crepes and a need of innovation to improve taste (such as creped and spicy). Conclusion of this social works shows that solid tofu’s waste can be used as base material to produce crepes, and the society group members are interested and are motivated.